Differences in Mathematical Communication Ability and Self-Efficacy of Students Taught With Team Assisted Individualization and Think Pair Share Cooperative Learning Models Assisted by Digital Books - Imaniyanti, Nur; Syahputra, Edi; Simamora, Elmanani (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study was to determine whether there were differences in mathematical communication skills and self-efficacy of students taught with the TAI type cooperative learning model and the TPS learning model assisted by digital books and to determine whether there was an interaction between initial mathematical abilities and learning models on mathematical communication skills and self-efficacy. This type of research is a quasi-experimental study conducted at SMKS Muhammadiyah 8 Medan. The results of the study showed that there were significant differences in students' mathematical communication skills between the group that followed learning with the TAI model and the group that followed learning with the TPS model. Students who learned with the TAI model showed higher mathematical communication skills compared to students taught with the TPS model. There was a significant difference in student self-efficacy between the TAI and TPS learning groups. Students in the TAI group had a higher level of self-efficacy than students in the TPS group. There was no significant interaction between initial mathematical abilities and learning models on students' mathematical communication skills and self-efficacy. This shows that the influence of learning models on mathematical communication skills and self-efficacy applies consistently at all levels of initial ability, whether high, medium, or low